PROHEALTH DIGITAL TRANSFORMATION: TIME EFFICIENCY IN DAILY CHECK-UPS FOR HIGH-RISK WORKERS AT PT PERTAMINA PATRA NIAGA REGIONAL SUMBAGUT - Ramadhani, Syaira Zhieka; Panjaitan, Juhri; Siregar, Anisa Putri; Simamora, Luthfiah Nazwa; Ramadhan, Ahmad Rezeki; BM, Bima Fadhilah; Utami, Tri Niswati (LPPM Univ. Ibn Khaldun Bogor, 2025)
The digital transformation of occupational health has led to various innovations that enhance efficiency, safety, and medical service quality. One notable breakthrough is ProHealth (Pertamina Robotic Health), developed by the Continuous Improvement Program (CIP) team at PT Pertamina Patra Niaga Region Sumbagut. This study examines the clinical impact and efficiency of using ProHealth as a daily health monitoring system (Daily Check Up/DCU) to strengthen the Fit To Work program in high-risk environments. Using a descriptive qualitative approach, data were collected through interviews, field observations, and document reviews involving medical staff and workers who routinely use the system. Findings reveal that ProHealthreduced average health check durations from 4 minutes 11 seconds to 1 minute 13 seconds per worker, eliminated overtime costs for medical teams, and minimized COVID-19 transmission risks through its fully automated, contactless operation. The system targets seven high-risk groups—security personnel, fuel truck drivers (AMT), heavy equipment operators, height workers, general drivers, confined space workers, and divers who face substantial occupational hazards. ProHealth enables real-time monitoring of physical conditions, increases readiness, and fosters a technology-driven safety culture. Overall, this innovation improves time and cost efficiency while strengthening the company’s Health, Safety, Security, and Environment (HSSE) framework through sustainable digital transformation.